Respuesta :
Answer:
Step-by-step explanation:
let fathers age now be x
daughters age now be y
10 years hence
(x+10)= 2(y+10)
x+10 = 2y+20
x-2y=10
10 years ago
(x-10)= 6(y-10)
x-10 = 6y-60
x-6y=-50
x-2y=10
x-6y=-50
subtract the equations
4y=60
y=15 daughter's age now
substitute y in x-2y=10
so x=40 present father's age
pls mark brainliest
Answer:
Let the age 10 years ago of daughter be ( x years ) and age of father would be ( 6x years )
After 10 years, age of father = ( 6x + 10 + 10 )
= ( 6x + 20 ) years
And Age of daughter will be = ( x + 10 + 10 )
= ( x + 20 ) years
ATQ,
6x + 20 = 2( x + 20 )
=> 6x + 20 = 2x + 40
=> 6x - 2x = 40 - 20
=> 4x = 20
=> x = 5
Hence, Present age of daughter = ( x + 10 )
= ( 5 + 10 )
= 15 years
Present age of father = ( 6x + 10 )
= 6( 5 ) + 10
= 30 + 10
= 40 years
Step-by-step explanation:
your answer Miss.